2011
DOI: 10.1016/j.plipres.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Docosapentaenoic acid (22:5n-3): A review of its biological effects

Abstract: This article summarises the current knowledge available on metabolism and the biological effects of n-3 docosapentaenoic acid (DPA). n-3 DPA has not been extensively studied because of the limited availability of the pure compound. n-3 DPA is an elongated metabolite of EPA and is an intermediary product between EPA and DHA. The literature on n-3 DPA is limited, however the available data suggests it has beneficial health effects. In vitro n-3 DPA is retro-converted back to EPA, however it does not appear to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
210
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(224 citation statements)
references
References 53 publications
5
210
0
9
Order By: Relevance
“…These effects were likely related to the production of resolvins and protectins (38,39,40,42). Moreover, it has been shown that n-3 DPA and MAG-DPA are likely metabolized by 5-LO, 15-LO, and CYP450 epoxygenase pathways in mediating these effects (12,27,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were likely related to the production of resolvins and protectins (38,39,40,42). Moreover, it has been shown that n-3 DPA and MAG-DPA are likely metabolized by 5-LO, 15-LO, and CYP450 epoxygenase pathways in mediating these effects (12,27,42).…”
Section: Discussionmentioning
confidence: 99%
“…EPA and DHA reduce the expression of genes for interleukin (IL-6, IL-8, and IL-1␤), vascular cell adhesion molecule-1, intracellular adhesion molecule-1, endothelial adhesion molecule, and E-selectin (9,13,52). However, docosapentaenoic acid (DPA; 22:5n-3) has not been studied extensively because of the limited availability of the pure compound (27). DPA is an elongated metabolite of EPA and is an intermediary product between EPA and DHA.…”
mentioning
confidence: 99%
“…Considerable amounts of ALA were metabolized to longer-chain n-3 fatty acids within the aorta, and a large proportion of ALA was converted to DPA. DPA has been associated with the inhibition of cyclooxygenase 1 activity, a decrease in cellular TNF-␣, and the induction of gene modulatory and anti-inflammatory effects (28,35,36). Additionally, n-3 fatty acids such as EPA and DHA are activators of peroxisome proliferator-activated receptors (PPARs).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that only a small amount of n-3 LCPUFA can be synthesized from the dietary precursor, at least in some women, a dietary source of n-3 LCPUFA is required during pregnancy and lactation to meet maternal and infant requirements. Although less is known about the role of DPA in fetal development, it has been suggested that there is some conversion to DHA and retro-conversion to EPA (Kaur et al 2011). There is also recent evidence that dietary intake of DPA is associated with neuroprotective effects (Kelly et al 2011) and heart health (Sun et al 2008), suggesting that DPA intake may have additional benefits if consumed during pregnancy and lactation.…”
Section: Introductionmentioning
confidence: 99%